The Role of Leader Member Exchange in Mediating the Effect of Empowerment on Employee Organization Commitments in Bali Beach Golf Course and Sector Restaurant Sanur, Bali - Cokorda Istri Agung Vera Nindiaputri; Ni Wayan Sitiari; Putu Ngurah Suyatna Yasa; Ni Putu Dita Ariyanti (JUSTBEST: Journal of Sustainable Business and Management, 2022)
This research aims to determine the leader member exchange mediates the effect of empowerment on employee organizational commitment at the Bali Beach Golf Course and Sector Restaurant in Sanur Bali. The population in this research were 146 employees at the Bali Beach Golf Course and Sector Restaurant. The sampling method is using by the saturated sample method, so that the entire population is used as a sample. The data was collected based on distributing questionnaires to employees at the Bali Beach Golf Course and Sector Restaurant. In testing the hypothesis was used path analysis techniques, with the AMOS (Analysis of Moment Structure) application version 16.0. The results showed that Empowerment had a positive and significant effect on leader exchange members at the Bali Beach Golf Course and Sector Restaurant in Sanur, Bali. Empowerment has a positive and significant effect on the organizational commitment of employees at the Bali Beach Golf Course and Sector Restaurant. Leader member exchange has a positive and significant effect on the organizational commitment of employees at the Bali Beach Golf Course and Sector Restaurant. Leader exchange members mediate the positive influence of empowerment on the organizational commitment of employees at the Bali Beach Golf Course and Sector Restaurant.